أثراستراتيجية ارسم أفكارك في الفهم القرائي عند تلميذات الصف الخامس الإبتدائي - محمود، بسهى عمران (الجامعة المستنصرية - كلية التربية الأساسية, 2019)
يهدف البحث الحالي إلى تعرف أثر استراتيجية أرسم أفكارك في الفهم القرائي عند تلميذات الصف الخامس الابتدائي. ولتحقيق ذلك اختارت الباحثة محافظة بغداد/ مديرية تربية الرصافة الأولى/ مدرسة الخنساء الابتدائية للبنات لتكون ميدانا لتطبيق تجربة البحث. وقد اعتمدت الباحثة على التصميم التجريبي ذا الضبط الجزئي لمجموعتين متكافئتين (التجريبية والضابطة) من ذوات الاختبار البعدي للفهم القرائي، وقد بلغت مجموعتي البحث (90) تلميذة من تلميذات الصف الخامس الابتدائي، وقد وزعن عشوائيا على مجموعتي (ضابطة وتجريبية) بواقع (45) تلميذة في المجموعة التجريبية و (45) تلميذة في المجموعة الضابطة. وبعد أن حددت الباحثة المادة العلمية التي ستدرسها في التجربة صاغت الأهداف السلوكية، فبلغ عددها (96) هدفا سلوكيا. وقد كافأت الباحثة بين مجموعتي التجربة (عينة الدراسة) احصائيا باستعمال الاختبار التائي (T—test) لعينتين مستقلتين ومربع كاي (كا2)، في متغيرات العمر الزمني محسوبا بالشهور، والتحصيل الدراسي للأبوين، واختبار الذكاء ل (رآفن)، ودرجات العام السابق للغة العربية (الصف الأول المتوسط)، قبل إجراء التجربة ولم تكن هناك فروق ذات دلالة إحصائية بين المجموعتين في هذه المتغيرات. ومن أجل تحقيق هدف البحث أعدت الباحثة اختبارا لقياس الفهم القرائي مكونا (27) فقرة اختبارية، استخرج صدقه بعرضه على نخبة من الخبراء والمحكمين، اما ثباته فقد استعمل معامل ارتباط الفا -كرونباخ، ولتحليل النتائج استعملت الباحثة اختبار (T—test) في معالجة نتائج التجربة احصائيا.
To achieve this, the researcher chose the governorate of Baghdad/ Directorate of Education of the first Rusafa/ Al-Khansaa Primary School for Girls to be a field for the application of the research experience. The researcher adopted the experimental design with partial control of two groups (Experimental and control) of the post¬test of reading comprehension, has reache The study groups (90) were students from the fifth grade primary school. They were randomly assigned to a group of 45 students in the experimental group and 45 students in the control group. After the researcher identified the scientific material to be studied in the experiment formulated behavioral goals, reaching the number (96) behavioral goals. The researcher was rewarded by using the T-test for two independent samples and the Kay box (Ka2) in the variables of the time-period calculated by months, the parents' academic achievement, the IQ test for RAFN. and the grades of the previous year of the Arabic language (First grade average), before the experiment and there were no statistically significant differences between the two groups in these variables. In order to achieve the objective of the research, the researcher prepared a test to measure the reading comprehension, consisting of (27) experimental paragraphs, extracted his honesty by presenting him to an elite group of experts and arbitrators, while his stability used the correlation coefficients of alpha-Cronbach. To analyze the results, the researcher used T- Results of the experiment statistically. At the end of the experiment, the researcher found that the students in the experimental group were superior to the students of the control group in the reading comprehension. The differences were statistically significant among the students of the two groups (experimental and control) and for the experimental group at 0.05 level
Keywords: الاستراتيجيات التعليمية -- الفهم القرائي -- اللغة العربية -- طلبة الصف الخامس الإبتدائي